Distinct Functions of Syntaxin-1 in Neuronal Maintenance, Synaptic Vesicle Docking, and Fusion in Mouse Neurons - Vardar, Gülçin; Chang, Shuwen; Arancillo, Marife; Wu, Yuan-Ju; Trimbuch, Thorsten; Rosenmund, Christian (The Journal of neuroscience, 2016)
Neurotransmitter release requires the formation of soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complexes by SNARE proteins syntaxin-1 (Stx1), synaptosomal-associated protein 25 (SNAP-25), and synaptobrevin-2 (Syb2). In mammalian systems, loss of SNAP-25 or Syb2 severely impairs neurotransmitter release; however, complete loss of function studies for Stx1 have been elusive due to the functional redundancy between Stx1 isoforms Stx1A and Stx1B and the embryonic lethality of Stx1A/1B double knock-out (DKO) mice. Here, we studied the roles of Stx1 in neuronal maintenance and neurotransmitter release in mice with constitutive or conditional deletion of Stx1B on an Stx1A-null background. Both constitutive and postnatal loss of Stx1 severely compromised neuronal viability in vivo and in vitro, indicating an obligatory role of Stx1 for maintenance of developing and mature neurons. Loss of Munc18-1, a high-affinity binding partner of Stx1, also showed severely impaired neuronal viability, but with a slower time course compared with Stx1A/1B DKO neurons, and exogenous Stx1A or Stx1B expression significantly delayed Munc18-1-dependent lethality. In addition, loss of Stx1 completely abolished fusion-competent vesicles and severely impaired vesicle docking, demonstrating its essential roles in neurotransmission. Putative partial SNARE complex assembly with the SNARE motif mutant Stx1A(AV) (A240V, V244A) was not sufficient to rescue neurotransmission despite full recovery of vesicle docking and neuronal survival. Together, these data suggest that Stx1 has independent functions in neuronal maintenance and neurotransmitter release and complete SNARE complex formation is required for vesicle fusion and priming, whereas partial SNARE complex formation is sufficient for vesicle docking and neuronal maintenance. Syntaxin-1 (Stx1) is a component of the synaptic vesicle soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex and is essential for neurotransmission. We present the first detailed loss-of-function characterization of the two Stx1 isoforms in central mammalian neurons. We show that Stx1 is fundamental for maintenance of developing and mature neurons and also for vesicle docking and neurotransmission. We also demonstrate that neuronal maintenance and neurotransmitter release are regulated by Stx1 through independent functions. Furthermore, we show that SNARE complex formation is required for vesicle fusion, whereas partial SNARE complex formation is sufficient for vesicle docking and neuronal maintenance. Therefore, our work provides insights into differential functions of Stx1 in neuronal maintenance and neurotransmission, with the latter explored further into its functions in vesicle docking and fusion.